Validity of the purchasing power parity in the selected European Union's countries: stationarity and cointegration approach - Chocholatá, Michaela, 1977-
Analýza parity kúpnej sily (purchasing power parity - PPP). Metodologické otázky. Testovanie, testy. Empirické výsledky.